Faecal prevalence, distribution and risk factors associated with canine soil-transmitted helminths contaminating urban parks across Australia. Issue 10 (September 2022) - Massetti, Luca; Wiethoelter, Anke; McDonagh, Phillip; Rae, Louise; Marwedel, Lara; Beugnet, Frederic; Colella, Vito; Traub, Rebecca J.
Graphical abstract: Highlights: Canine soil-transmitted helminths (cSTHs) were found in 42.7% of parks in Australia. Hookworms represent the most common cSTHs contaminating parks in Australia. Contamination with cSTHs is strongly associated with socioeconomic-related factors. Abstract: Dog parks provide an ideal urban space where dogs and their owners can exercise, play, and socialise in a safe environment. However, these parks can also increase the risk of exposure to a series of infectious agents including canine soil-transmitted helminths (cSTHs) such as hookworms, roundworms, Strongyloides stercoralis, and Trichuris vulpis, which are endemic to Australia. In this study, we collected 1581 canine faecal samples in 190 urban parks across Australia and subjected these to faecal floatation and multiplex real-time PCRs (qPCR) to detect a range of cSTHs. In total, 44.2% of the parks sampled were contaminated with at least one species of cSTH, with hookworms being the most prevalent parasites (10.2%) followed by Trichuris spp. (1.3%) and Strongyloides spp . (1.2%). This is the first large-scale study investigating the contamination of urban parks with cSTHs in Australia, and the first nation-wide study to demonstrate the occurrence of Strongyloides spp. in canine faecal samples from urban areas in the country. This study reveals a high rate of contamination with cSTHs in dog parks in urban Australia, most of which having proven zoonotic potential. Preventive measures, including awareness-raising educational programmes promoting responsible pet ownership, should be encouraged to minimise the health risks associated with cSTHs for both dogs and humans.